Peningkatan Proses dan Hasil Belajar IPAS Menggunakan Model Problem Based Learning Berbantu Media Wordwall - Edi, Mukhamad; Subhanadri; Habibie, Zulqoidi R. (Master of Civic Innovation and Education Technology, 2025)
This study aims to develop the IPAS learning process and outcomes through the application of the Problem-Based Learning model supported by Wordwall media in fifth-grade students at Sijau 224/II Public Elementary School who have low learning completeness (41.38%). The research used a two-cycle Classroom Action Research (CAR) design with a sample of 22 fifth-grade students. Data collection techniques were carried out through observation of learning activities and learning outcome tests, analyzed qualitatively and quantitatively with stages of planning, implementation, observation, and reflection. The results showed a significant increase in teacher learning activities from 87.5% to 95%, student learning processes from 59.47% to 81.03%, and IPAS learning achievement from 69.23% in cycle I to 88.46% in cycle II. The Problem-Based Learning model supported by Wordwall media proved effective in creating interactive learning and increasing student engagement in problem solving. The implications of this research provide creative learning methods that can be replicated to improve the quality of IPAS learning at the elementary education level.